Urban green infrastructure: bridging biodiversity conservation and sustainable urban development through adaptive management approach - Wang, Dong; Xu, Pei-Yuan (Frontiers in Ecology and Evolution, 2024)
Urban green infrastructure (UGI) is pivotal in reconciling biodiversity conservation with sustainable urban development through adaptive management approaches. This paper introduces a comprehensive conceptual framework integrating ecological principles, urban planning strategies, and adaptive management methodologies to nurture resilient and biodiverse urban landscapes. The essence of UGI lies in its capacity to bolster ecological connectivity, restore ecosystem functions, and provide habitats for diverse flora and fauna within urban settings. Fundamental principles governing UGI design underscore its multifunctionality, connectivity, diversity, and accessibility, emphasizing the importance of adaptive management marked by its iterative and participatory nature. Despite challenges posed by urbanization, such as habitat loss, pollution, and climate change, UGI interventions offer promising avenues for enhancing habitat quality, connectivity, and ecosystem resilience. Global case studies demonstrate the effectiveness of UGI in biodiversity conservation, leveraging initiatives like green roofs, urban forests, and community gardens. UGI significantly contributes to sustainable urban development by offering diverse ecosystem services across various domains. Adaptive management is critical for effective UGI planning and implementation, ensuring flexibility amidst evolving environmental conditions. However, UGI encounters hurdles, including funding constraints, institutional fragmentation, and equity issues. Addressing these challenges necessitates innovative financing mechanisms, community involvement, and policy innovations. UGI presents a transformative pathway towards fostering resilient, biodiverse, and sustainable urban landscapes, imperative for cities to thrive in the 21st century.